Homozygous familial hypercholesterolemia in Italy: Clinical and molecular features. (November 2020) - Bertolini, Stefano; Calandra, Sebastiano; Arca, Marcello; Averna, Maurizio; Catapano, Alberico L.; Tarugi, Patrizia; ,; Bartuli, Andrea; Bucci, Marco; Buonuomo, Paola Sabrina; Calabrò, Paolo; Casula, Manuela; et al.
Abstract: Background and aims: Homozygous familial hypercholesterolemia (HoFH) is a rare genetic disorder characterized by extremely elevated plasma levels of low density lipoprotein cholesterol (LDL-C) and high risk of premature atherosclerotic cardiovascular disease (ASCVD). HoFH is caused by pathogenic variants in several genes, such as LDLR, APOB and PCSK9, responsible for autosomal dominant hypercholesterolemia (ADH), and LDLRAP1 responsible for autosomal recessive hypercholesterolemia (ARH). Aim of this study was the review of the clinical and molecular features of patients with HoFH identified in Italy from 1989 to 2019. Methods: Data were collected from lipid clinics and laboratories, which had performed molecular diagnosis in suspected HoFH. Clinical data included baseline lipid levels and ASCVD events. Results: A total of 125 subjects with ADH were identified, of whom 60 were true homozygotes, 58 compound heterozygotes and 7 double heterozygotes for LDLR (likely) pathogenic variants. Compared with compound heterozygotes, true homozygotes showed a more severe lipid phenotype and more ASCVD events. ADH carriers of LDLR negative variants ( R -NEG) presented with a more aggressive phenotype, as compared to carriers of LDLR defective variants ( R -DEF). Kaplan-Meier analysis showed that the median age of ASCVD event-free survival was 25 years of age in R -NEG as opposed to 50 years of age in R -DEF patients. A total of 66 patients with ARH were also identified, of whom 46 were homozygotes and 20 compound heterozygotes. The phenotypic features of ARH patients were similar to those of R -DEF/ADH patients. Overall, 45% ADH patients and 33% ARH patients did not meet the classic diagnostic criteria for HoFH. Conclusions: In our cohort, the phenotypic variability of HoFH was dependent on the candidate gene involved and the functional impact of its variants on the LDL receptor pathway. Graphical abstract: Image 1 Highlights: Characterization of 125 homozygotes with autosomal dominant hypercholesterolemia (ADH). Approximately 98% of ADH patients carried (likely)/pathogenic variants of LDLR gene. Identification of 90 different LDLR variants with variable phenotypic expression. Characterization of 66 homozygotes with autosomal recessive hypercholesterolemia (ARH). Sixty-four ARH patients carried the two LDLRAP1 variants previously found in Sardinia.